Solve the following time complexities
a) T (n)= n∑ n∑ 1
i=1 j=1
b) T(n) = n-1 ∑ n∑ c
i= 0 j= i+1
c) T(n) = n ∑ 1
i= 1
a) "T(n)=n\\Sigma n\\Sigma 1"
We know that,
"\\Sigma 1= n"
So, "\\Sigma n\\times n=\\Sigma n^2"
Here first term of series n, will be functioning as the constant,
So, "\\Sigma n^2 = \\frac{n(n+1)(2n+1)}{6}"
"\\Rightarrow T(n)=n( \\frac{2n^3+n^2+2n^2+n}{6})"
"\\Rightarrow T(n)=\\frac{2n^4+3n^3+n^2}{6}"
"\\Rightarrow T(n)=\\frac{n^4}{3}+\\frac{n^3}{2}+\\frac{n^2}{6}"
Hence the complexity of the given terms will be
"=O(n^4)+O(n^3)+O(n^2)"
Hence the complexity of the terms will be "O(n^4)"
b) "T(n)= (n-1)\\Sigma n \\Sigma c"
Here c is constant,
"\\Sigma c = c\\Sigma1 = cn"
"\\Sigma n(cn)=c\\Sigma n^2 =c\\frac{n(n+1)(2n+1)}{6}"
"=\\frac{c (n-1)(n^2+n)(2n+1)}{6}"
"=\\frac{c(n-1)(2n^3+n^2+2n^2+n)}{6}"
"=\\frac{c(2n^4+3n^3+n^2-2n^3-3n^2-n)}{6}"
"=\\frac{c(2n^4+n^3-2n^2-n)}{6}"
Hence, the respective time complexity of the given function,
"=O(n^4)+O(n^3)-O(n^2)+O(n)"
Hence the complexity of the given function will be "O(n^4)"
c)
"T(n)=n\\Sigma 1"
"=n\\times n"
"=n^2"
Hence, the time complexity of the given function will be "O(n^2)"
Comments
Leave a comment